A One Health Approach to Tackle Cryptosporidiosis. Issue 3 (March 2020) - Innes, Elisabeth A.; Chalmers, Rachel M.; Wells, Beth; Pawlowic, Mattie C.
Abstract : Cryptosporidiosis is a significant diarrhoeal disease in both people and animals across the world and is caused by several species of the protozoan parasite Cryptosporidium. Recent research has highlighted the longer-term consequences of the disease for malnourished children, involving growth stunting and cognitive deficits, and significant growth and production losses for livestock. There are no vaccines currently available to prevent the disease and few treatment options in either humans or animals, which has been a significant limiting factor in disease control to date. A One Health approach to tackle zoonotic cryptosporidiosis looking at new advances in veterinary, public, and environmental health research may offer several advantages and new options to help control the disease. Highlights: Development of new vaccines for livestock and people to reduce disease and shedding of Cryptosporidium oocysts is a key One Health goal. An integrated genotyping approach to detect and differentiate Cryptosporidium parasites in both veterinary and public health will inform source tracking, epidemiology, and surveillance. The application of relevant clinical in vivo models and novel in vitro systems will progress understanding of host–pathogen interactions and enable efficacy testing of new therapeutics and vaccines. New methods to treat Cryptosporidium -contaminated livestock and human waste will reduce oocyst contamination of the environment and help protect water catchments. Knowledge exchange and education are vital to encourage a One Health approach to tackle cryptosporidiosis.